KONSEP TASWIYAH AL-NAFS DALAM PENGEMBANGAN PRIBADI MANUSIA - Hamdie, Ilham Masykuri (UIN Antasari, 2017)
The manifestation of human superiority as ‘ahsan al-taqwim’ can be interpreted as the process of developing the level of